2018
DOI: 10.3390/nu10121865
|View full text |Cite
|
Sign up to set email alerts
|

Association between the Portion Sizes of Traditional Japanese Seasonings—Soy Sauce and Miso—and Blood Pressure: Cross-Sectional Study Using National Health and Nutrition Survey, 2012–2016 Data

Abstract: While previous studies have reported the association between food portion size and health outcomes, the association between food seasonings and blood pressure (BP) has not been clarified. This study aimed to investigate the association between the portion sizes of traditional Japanese seasonings and BP. Data on 25,738 Japanese participants (10,154 men and 15,584 women) aged ≥20 years registered in the 2012–2016 National Health and Nutrition Survey (NHNS) were used for this cross-sectional study. The portion si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
8
0
2
Order By: Relevance
“…In particular, traditional Japanese seasonings such as shoyu (soya sauce) and miso (fermented soya bean paste) have a higher Na content than other seasonings (36) . However, we previously noted that, based on the NHNS data, larger portion sizes of soya sauce or miso were not associated with elevated BP levels among Japanese adults who typically have a higher intake of vegetables, soya products and mushrooms (14) . In contrast, the food source of salt varies with age; for example, the proportion of adults consuming miso was higher in the elderly, and the proportions of those consuming Chinese noodles and Japanese curry roux were higher among the younger age groups (37) .…”
Section: Discussionmentioning
confidence: 89%
“…In particular, traditional Japanese seasonings such as shoyu (soya sauce) and miso (fermented soya bean paste) have a higher Na content than other seasonings (36) . However, we previously noted that, based on the NHNS data, larger portion sizes of soya sauce or miso were not associated with elevated BP levels among Japanese adults who typically have a higher intake of vegetables, soya products and mushrooms (14) . In contrast, the food source of salt varies with age; for example, the proportion of adults consuming miso was higher in the elderly, and the proportions of those consuming Chinese noodles and Japanese curry roux were higher among the younger age groups (37) .…”
Section: Discussionmentioning
confidence: 89%
“…Although the mineral potassium is present in high quantity in soybeans, and it has been found to decrease during fermentation, miso is still considered a good source containing between 0.2 and 0.44 g/100 g (Kwon et al., 2010; Okada et al, 2018). Evidence has shown that increased potassium intake reduces blood pressure and is associated with a lower incidence of stroke (Aburto et al., 2013).…”
Section: Potential Health Benefits Of Japanese Koji and Misomentioning
confidence: 99%
“…Dietary sodium intake is much higher in the Japanese population than in Western countries, and the majority of it comes from seasoning. However, a study by Okada et al [ 71 ] has shown that the portion size of soy sauce or miso is not associated with hypertension. These results were based on 25,738 Japanese men and women aged 20 years or older who participated in the national health and nutrition surveys between 2012 and 2016.…”
Section: Nutritional Function Of Misomentioning
confidence: 99%